Connecting the Dots Between Mindset and Impostor Phenomenon, via Fear of Failure and Goal Orientation, in Working Adults - Noskeau, Rebecca; Santos, Angeli; Wang, Weiwei (Frontiers in Psychology, 2021)
This study aims to investigate the relationship between mindset and impostor phenomenon, via the explanatory role of fear of failure and goal orientation in the work domain. Only one known study has previously connected mindset and impostor phenomenon in the scientific literature among females in a university setting. Data was collected from 201 working adults, with a roughly equal male-female ratio, from a range of sectors in the UK, Ireland, and the US. Participants completed an online survey comprising the Implicit Theories of Intelligence Scale, the Performance Failure Appraisal Inventory, Work Domain Goal Orientation Instrument, and the Clance Impostor Phenomenon Scale. We tested a parallel-serial mediation model using structural equation modelling. The results suggest that people with a fixed mindset tend to experience more impostor phenomenon at work and this relationship is predominantly explained by their fear of failure. Further, when employees are also motivated by a performance avoid goal orientation, the relationship increases in strength. This indirect relationship suggests that staff training, and coaching interventions designed to increase people's belief that they can develop their abilities results in a reduction of their fear of failure and in their motivation to want to avoid showing their inability at work. The results also suggest cultivating environments that promote a growth mindset and learning goal orientation, alongside the safety to fail, could lessen the negative effects of having a fixed mindset, reduce fear of failure, and alleviate impostor phenomenon’s negative impact on employee career development and wellbeing.